The Employment of Low-Skilled Immigrant Men in the United States - Duncan, Brian; Trejo, Stephen J (American Economic Review, 2012)
Using microdata from the 2000 Census, we analyze how the employment rates of foreign-born and US-born men vary with education. After a period of adjustment during the first few years upon arrival, the overall employment rate of immigrant men quickly approaches that of US natives. Among those with the lowest education levels, immigrants exhibit substantially higher rates of employment than comparable natives. This pattern is consistent with a simple theoretical model of migrant selectivity that jointly considers a potential migrant's decisions regarding where to locate and whether to work.